Effects of Workplace Intervention on Affective Well-being in Employees’ Children - Lawson, Katie M. (Dev Psychol, 2016)
Using a group-randomized field experimental design, this study tested whether a workplace intervention – designed to reduce work-family conflict – buffered against potential age-related decreases in the affective well-being of employees’ children. Daily diary data were collected from 9-17 year old children of parents working in an information technology division of a U.S. Fortune 500 company prior to and 12-months after the implementation of the Support-Transform-Achieve-Results (STAR) workplace intervention. Youth (62 with parents in the STAR group, 41 in the Usual Practice group) participated in eight, consecutive, nightly phone calls during which they reported on their daily stressors and affect. Well-being was indexed by positive and negative affect and affective reactivity to daily stressful events. The randomized workplace intervention increased youth positive affect and buffered youth from age-related increases in negative affect and affective reactivity to daily stressors. Future research should test specific conditions of parents’ work that may penetrate family life and affect youth well-being.